THE IMPACT OF CREDIBILITY, INFORMATIVE, AND HEDONIC/PLEASURE ON YOUTH CONSUMERS’ ATTITUDE TOWARDS ADVERTISING: STUDY OF MOBILE ADVERTISING - Sebastian, Sondakh David Reynaldo (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
The mobile media will be the primary focus of this study due to the rapid growth of mobile devices users each year and simply the huge number of mobile devices users which already in the billions of users. Because of this number of user, it results in huge number of advertisement delivered. That is why it is important to understand the consumers’ attitude towards advertising. Based on previous research regarding attitude towards advertising, a questionnaire was created to identify the relationships between independent and dependent variables. 100 youth participated in the survey. The results show that, generally, youth mobile users have moderate attitude towards advertising. Users have neutral perception regarding the credibility of advertisement. The most important aspect is how informative the advertisement is and how entertaining that advertisement is. Recommendations are advertiser should provide useful information and try to be entertaining in advertisements.   Keywords: mobile advertising, credibility, informative, hedonic, pleasure, consumers’ attitude